The Effect of Earning Per Share (EPS), Return On Equity (ROE), and Net Profit Margin (NPM) on the Stock Price of Manufacturing Companies Listed on the BEI Period 2017 - 2019 - Ayu Putri Lestari; Ratna Wijayanti Daniar Paramita; Muhammad Mudhofar (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
The purpose of this study was to examine the effect of Earning Per Share (EPS), Return On Equity (ROE) and Net Profit Margin (NPM) on stock prices in manufacturing companies listed on the IDX for the 2017-2019 period. Sampling was carried out using purposive sampling method, and obtained 97 manufacturing companies multiplied by 3 years so as to obtain a sample of 291 companies used as samples in this study. The secondary data source in this study comes from the IDX. The analysis technique in this study uses multiple linear analysis. Based on partial results show that Earning Per Share (EPS) has a significant effect on stock prices, Return On Equity (ROE) has a significant effect on stock prices and Net Profit Margin (NPM) has no effect on stock prices.